Menguak profile komunitas pegunungan transisi dan problematiknya dalam pembangunan - Ashari (Research Agency for Humanity and Urban, 2025)
This research was conducted in the Pengkasalu community in Kaili Village, West Suli District, Luwu, South Sulawesi. The Pengkasalu community is a transitional mountain community. It is called a transitional mountain community because the Pengkasalu area is located at the foot of a mountain, and transitional because its people are touched by modern culture but still bound by traditional values. This research employed a qualitative, descriptive approach. The results indicate that the Pengkasalu community is located at the foot of a mountain, isolated from outside activity centers. Its livelihood is farming. However, along with social changes, the community has experienced social problems (secularism, a pragmatic life orientation, and a distance from traditional and religious values) that have long been inherent in the local cultural heritage.